Cost Control Strategy in Covid-19 Pandemic Using Balanced Scorecard at Yogyakarta Islamic Hospital PDHI - Cahyo Prihatmoko; Kusbaryanto Kusbaryanto; Nur Hidayah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The hospital is at the forefront to overcome the covid outbreak but the personal protective equipment (APD) is getting rare. This makes health service management more ineffective and efficient. The purpose of this study is to develop a cost control strategy to maintain and even improve hospital performance during Pandemi Covid-19. This research is a qualitative research with a case study approach conducted at PDHI Yogyakarta Islamic Hospital. The research design uses an approach to explore and understand the organization by presenting a comprehensive picture and reporting a detailed description of the source of information and preparing it without the intervention of the researchers. The interview was conducted to the Chairperson of the PDHI Foundation, the Chairperson of the Supervisory Board, and the Hospital Director. The data analysis used includes compaction, coding, and identification of themes to get a deeper understanding of strategic planning at RSIY PDHI. The overall strategic objective of the organization is categorized into 4 (four) perspectives, namely financial goals, customer goals, internal business processes, and the purpose of growth and learning. In terms of financial, three strategic objectives are set, namely income growth, cost reduction, and increased profitability. From the customer side, four strategic objectives are set, namely improving the quality and quality of service, increasing customer satisfaction, improving the quality of customer relations, and improving the image of the hospital. In terms of internal business processes, three strategic objectives are set, namely the integration of internal service processes, improving the quality of service processes to customers, and increasing the speed of the service innovation process. PDHI Yogyakarta Islamic Hospital is advised to improve a strategic plan with a framework of the Balanced Scorecard that has been previously created. Keywords: Balanced Scorecard, Cost Control Strategy, PDHI Islamic Hospital Yogyakarta